The Influence Of Leadership Style, Bureaucratic Reform, And Work Motivation On Work Ethic And Its Impact On Public Service At The Depok District Attorney's Office West Java - Sutoro, Moh; Sari, Ratna (Sean Institute, 2024)
This study aims to analyze the influence of Leadership Style, Bureaucratic Reform, and Work Motivation on Work Ethic and its impact on the quality of Public Service at the Depok District Attorney's Office. This research employs a descriptive quantitative method, with data collected through questionnaires distributed to 107 respondents. The data were analyzed using multiple linear regression to examine the influence of independent variables on Work Ethic and Public Service. The results show that Bureaucratic Reform and Work Motivation have a significant positive impact on Work Ethic, while Leadership Style does not show a significant influence. The study also emphasizes that a strong Work Ethic is a key factor in improving the quality of Public Service. Therefore, a comprehensive management strategy, including participative leadership, continuous bureaucratic reform, and an integrated motivation program, is essential to enhance employee performance and the quality of services provided to the public.